Antineutrophil cytoplasmic antibody (ANCA) testing: Audit from a clinical immunology laboratory. (26th July 2016) - Phatak, Sanat; Aggarwal, Amita; Agarwal, Vikas; Lawrence, Able; Misra, Ramnath
Abstract: Aim: Anti‐neutrophil cytoplasmic antibodies (ANCA) are associated with small vessel vasculitis now termed 'ANCA associated vasculitis' (AAV). ANCAs are reported in diverse diseases where they have no clinical utility. We carried out an audit in a clinical immunology laboratory and assessed if use of ordering practices could have improved utility of ANCA. Methods: All samples received for ANCA testing during 2014 were tested by indirect immunofluorescence (IIF) and automated enzyme‐linked immunosorbent assay (ELISA). Clinical records of all samples positive by one or more assays were retrieved. We assessed the effect of applying proposed test ordering guidelines on performance of the tests. Results: Of 1590 samples, 108 (6.8%) had a positive result by at least one method. IIF showed perinuclear pattern in 72 (21 were antinuclear antibody positive), cytoplasmic in 22, six had atypical pattern and eight were negative. By ELISA anti‐myeloperoxidase antibodies were present in 33 samples, anti‐proteinase 3 in 24, while five sera had both antibodies. ELISA and IIF were concordant in 45 samples. Twenty‐seven patients had AAV of which 23 were both ELISA and IIF positive. Among these 27 with AAV all had at least one ordering criteria, while in 81 patients without AAV but with positive test, 38 had no ordering criteria. Conclusion: Reduction in false positive can be achieved by considering only those samples as ANCA positive that test positive both on IIF and ELISA and by following ordering guidelines before requesting ANCA testing, and by use of ordering criteria by clinicians.